2014
DOI: 10.1111/ans.12601
|View full text |Cite
|
Sign up to set email alerts
|

Time delays in presentation and treatment of acute scrotal pain in a provincial hospital

Abstract: Delay from the time of testicular pain until surgical exploration is important for the chances of testicular salvage and is made up mostly of pre-hospital delays. Patients under the age of 14 had longer delays pre-hospital.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
11
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 12 publications
2
11
0
Order By: Relevance
“…In addition to in-hospital time (T2), we found that time between ultrasonography and operating theatre (T4) were also longer in the orchiectomy group (p < .05). These results suggest that the use of ultrasound delays time of operation and increases the rate of orchiectomy, which is in line with data in literature [9,10,28]. As in-hospital time is an important factor in testicular survival, scoring systems like the TWIST score seem to be interesting to shorten the time to surgery [21].…”
Section: Influence Of Prehospital and In-hospital Times On Testicularsupporting
confidence: 88%
See 3 more Smart Citations
“…In addition to in-hospital time (T2), we found that time between ultrasonography and operating theatre (T4) were also longer in the orchiectomy group (p < .05). These results suggest that the use of ultrasound delays time of operation and increases the rate of orchiectomy, which is in line with data in literature [9,10,28]. As in-hospital time is an important factor in testicular survival, scoring systems like the TWIST score seem to be interesting to shorten the time to surgery [21].…”
Section: Influence Of Prehospital and In-hospital Times On Testicularsupporting
confidence: 88%
“…Castañeda-S anchez et al [31] reported that inhospital times were 5.57 h in the orchiectomy group and 3.6 h in the salvaged group. We also found that in-hospital times (T2) were longer in the orchiectomy group (4.1 h) than in the salvaged group (2.6 h) as described in literature [9,28].…”
Section: Influence Of Prehospital and In-hospital Times On Testicularsupporting
confidence: 83%
See 2 more Smart Citations
“…1,4 It is recognised that there is a 4-8-hour window before significant ischaemic damage occurs in testicular torsion, 5,6 resulting in morphological changes in testicular histopathology and impaired spermatogenesis. 6,7 Delayed exploration leads to increased orchidectomy rates 6,8 and it would therefore follow that patients being transferred from regional hospitals to tertiary paediatric surgical centres are potentially at increased risk of testicular loss. 9 In the UK, this has resulted in the recommendation that these transfers should occur as an exceptional circumstance and that exploration should be undertaken in the presenting hospital.…”
mentioning
confidence: 99%